Evaluation of sensitivity, motor and pain thresholds across the menstrual cycle through medium-frequency transcutaneous electrical nerve stimulation (Clinics, 2013)
OBJECTIVES: The aim of this study was to identify variations in nervous thresholds in different phases of the menstrual cycle in eumenorrheic women and users of oral contraceptives. METHOD: An observational study was performed including 56 volunteers, consisting of 30 eumenorrheic women who were non-users of oral contraceptives and 26 users of oral contraceptives. An electrical stimulator was employed to assess their nervous thresholds, with pulses applied at a fixed frequency of 2,500 Hz, modulated at 50 Hz, with phase variances of 20 μs, 50 μs and 100 μs. Sensitivity, motor and pain thresholds were evaluated during five menstrual cycle phases: phase 1 - menstrual, phase 2 - follicular, phase 3 - ovulatory, phase 4 - luteal and phase 5 - premenstrual. RESULTS: The results indicated low sensitivity thresholds of 100 μs for non-users of oral contraceptives and 50 μs for oral contraceptive users in phase 5. Low motor thresholds of 20 μs, 50 μs and 100 μs were observed for non-users of oral contraceptives in phase 5, while that of oral contraceptive users was 100 μs. Finally, a low pain threshold of 100 μs was observed in phase 5, but only in the oral contraceptive group. CONCLUSION: Nervous thresholds vary systematically across the phases of the menstrual cycle, with or without the use of oral contraceptives. These variations should be taken into account during research performed in women.